Bibliometrijska analiza revije Knjižnice v obdobju 2011-2016 - Zupančič, Anika (Knjižnica, 2017)
Purpose: At the occasion of 60th anniversary of Library - the Slovenian professional journal in the field of library and information science a bibliometric analysis of the journal was made encompassing the period of the last six years (2011-2017). This paper reports on the results of a quantitative bibliometric analysis thus continuing previous bibliometric analyses of the journal. Methodology/approach: The results give information about authors, authors' institutions and countries, and include the analysis of bibliographic sources cited in journal articles. Only "research" papers were analysed. Results: The results point to: (1) the volume of articles in the period from 2011 to 2016, (2) the authorship productivity, identification and listing of core authors; (3) the authorship and co-authorship pattern; (4) the subject areas of published papers; (5) the citation analysis of references used in the articles and the analysis of distribution of the age of citations. Research limitations: Due to the amount of papers dealing with library history, some of the analyses were hard to perform. Originality/practical implications: The contribution provides an overview of the current state of LIS research journal articles in Slovenia, focusing on the data that may be collected by surveying the issues of the journal in the given period of time.
Keywords: analiza citiranja; bibliometric analysis; bibliometrics; bibliometrija; bibliometrijska analiza; citation analysis; journal Library; revija Knjižnica; scientific journals; strokovne revije